Magnesium sulfate is not used for pre-eclampsia and eclampsia in Mexico and Thailand as much as it should be - Pisake Lumbiganon; A Metin Gülmezoglu; Gilda Piaggio; Ana Langer; Jeremy Grimshaw
OBJECTIVE: In the past ten years effective treatments for pre-eclampsia and eclampsia have been evaluated and identified following large trials and systematic reviews. We investigated the extent of those effective interventions' implementation. METHODS: Descriptive analysis of data collected as part of a cluster randomized trial. The trial was assigned the International Standardised Randomized Controlled Trial Number ISRCTN 14055385. Hospitals with more than 1000 deliveries per year not directly associated with an academic institution in Mexico City municipal area in Mexico (n = 22) and the north-east region of Thailand (n = 18) were included. All women delivering at the participating hospitals at two time periods in 2000 and 2002 contributed data on practice rates. The use of magnesium sulfate for pre-eclampsia and eclampsia were the outcomes. FINDINGS: Eight out of 22 hospitals in Mexico (range 0.8% to 8.5%) and all 18 hospitals in Thailand (range 18.6% to 63.6%) used magnesium sulfate for women with pre-eclampsia. In Mexico, 11 of 22 hospitals used magnesium sulfate for eclampsia (range 9.1% to 60.0%). In Thailand, all 17 hospitals having eclampsia cases used magnesium sulfate (range 25% to 100%). CONCLUSION: Despite compelling evidence, magnesium sulfate use is below desired levels. Clinical practices should be audited and implementation of this effective intervention should be taken up as a priority where universal implementation is not in place.